The Implementation of FT-IR Method for Compound Detection in Eco-Enzyme Applied as Hydrogel Patch - SetiyaNingrum, Diah Ayu; Nutfindiani, Elvi Diah; Margaretha, Zahra; Efendi, Meilisa Rusdiana Surya (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Potential organic waste includes fruit and vegetable peels which are used as eco-enzyme which are rich in benefits in several fields, one of which is in the health sector, namely hydrogel patch. The aim of this research is to identify the compound content in eco-enzyme and understand the impact of hydrogel patch on the process. healing open wounds. The research method used is the FT-IR method to detect the compound content of eco-enzyme which are applied as hydrogel patchs to heal open wounds in mice. The conclusion in this research is that the presence of flavonoid, alkaloid and tannin compounds in eco-enzyme has been identified and shows that the 5 treatments on eco-enzyme hydrogel patch have concentrations of 25%, 35% and 45% which are stable or 100% recovery, because the results One-Way ANOVA analysis in pre-clinical hydrogel patchs on mice in open wound healing showed a sig value of p = 0.283 > α (0.05). The analysis results show that the functional group (OH) appears at an absorption of 3293.56 cm-1, at an absorption of 2174.49 cm-1 it shows the presence of an Alkyl Nitrile functional group, the Amide functional group (CN) is found at an absorption of 1636.34 cm-1.